2001
DOI: 10.1080/030097401750065292
|View full text |Cite
|
Sign up to set email alerts
|

Eighteen years follow-up study of the clinical manifestations and progression of Dupuytren's disease

Abstract: The incidence of Dupuytren's disease is high in elderly men. Dupuytren's disease is progressive in nature and most operated patients have recurrent finger contractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Dupuytren’s disease (DD) is extremely common and is estimated to affect approximately 4% of the general UK and US populations 1 . Between 35–50% of patients with early DD manifest as nodules on the palmar aspect of the hand go on to develop finger contractures 2 , 3 . The nodules are typically quiescent for a period and then become active, progressing to flexion deformities over a period of months 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Dupuytren’s disease (DD) is extremely common and is estimated to affect approximately 4% of the general UK and US populations 1 . Between 35–50% of patients with early DD manifest as nodules on the palmar aspect of the hand go on to develop finger contractures 2 , 3 . The nodules are typically quiescent for a period and then become active, progressing to flexion deformities over a period of months 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However they all suffer from disadvantages. The ideal would be a treatment that prevents progression in the 30–50 % [ 5 , 6 ] of at risk patients with early DD. A variety of treatments have been proposed for early DD but there is currently no clear evidence for their role and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be difficult to ascribe nodule resolution to treatment as nodules have been reported to regress spontaneously. An epidemiological study conducted in Iceland reported that of 56 men initially noted to have nodules or cords, 8 were judged to have normal hands 18 years later [ 5 ]. The variation in diagnostic criteria for DD has been noted [ 3 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 35–50% of patients with early DD manifest as nodules on the palmar aspect of the hand go on to develop finger contractures 2, 3 . The nodules are typically quiescent for a period and then become active, progressing to flexion deformities over a period of months 4 .…”
Section: Introductionmentioning
confidence: 99%